To convert the quadratic from vertex form to standard form, we need to expand the equation.
Starting with the vertex form: y = 2(x−5)2 − 10
Expanding the binomial square: y = 2(x−5)(x−5) − 10
Expanding further: y = 2(x^2 − 10x + 25) − 10
Distributing the 2: y = 2x^2 − 20x + 50 − 10
Combining like terms: y = 2x^2 − 20x + 40
The standard form of the quadratic is y = 2x^2 − 20x + 40.
Convert the quadratic y = 2(x−5)2 − 10 from vertex form to standard form.(2 points) The standard form of the quadratic is y= x2+ x+ .
1 answer